Gene Expression and Antioxidant Effects of Cinnamon (Cinnamomum Zeylanicum, Breyne) in Alloxan -Induced Diabetic Rats - Hayder Ghazi Abdulshaheed; Haidar K.A.Alsaedi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background and Aim: In this study rats, a systematic analysis was conducted to examine the antioxidantproperties of cinnamon (Cinnamomum Zeylanicum, Breyne) in controlling high blood sugar levels, and apharmacological comparison made to investigate whether or not it had a positive effect on the antioxidantsystem.Materials and Methods: Alloxan 60 mg injected into the marginal ear veins of eighteen diabetic rats Afterthis diabetic animal study, the rats were randomly assigned to 4 groups. There were six animals in each ofthe 4 groups: Group 1(C): Positive control, Received orally 5 ml normal saline (0.9% NaCl) daily. Group2(D): Negative control, Diabetes rats only, received single-dose alloxan 60 mg/kg body weight. Group3(K): Diabetes rats, received cinnamon orally 35 mg/kg body weight dissolved in 2 ml normal. Group 4(I):Diabetes rats, was given 2 I.U/ animal of insulin subcutaneously daily.Results: All animal groups were treated for four weeks.Blood samples were taken from these groups weeklyfor biochemical analysis to estimate: Blood glucose malondialdehyde(MDA), Glutathione (GSH). Theresults showed high glucose and MDA concentration associated with an increased oxidant stress alloxaninduces on diabetic animals. The statistical analysis showed that a cinnamon significant (P<0.05) reductionin glucose, MDA,GSH comparison with positive control. The level of MDA, GSH was also significantlyreduced (P<0.05) in all period comparison with the period before treated with Cinnamon extract .there was4.3-fold more Ins I upregulated in the Cinnamon -treated diabetic rats 35 percent of the control group wereheterozygous and three percent of the experimental group were mutant for that trait.Conclusion: Furthermore, Cinnamon-treated diabetic rats (group K) showed a significant increase inthe activities of both enzymatic and non-enzymatic antioxidants with concomitant overexpression ofinsulin I genes when compared to diabetic control rats (group D). Cinnamon contains antioxidants andantihyperglycemic effects at the end of the experiment.